A SEMIOTIC ANALYSIS FOUND IN KUDETA BALI ADVERTISEMENTS - Ni Ketut Ria Agustina; I Dewa Ayu Devi Maharani Santika; Desak Putu Eka Pratiwi (ID Solutions, 2021)
The aims of the study are to identify the verbal and non-verbal signs as well as to analyze their meaning in Kudeta Bali advertisements. Advertisements usually contain with sign whether in verbal or non-verbal. Each of them is used to express the meaning intended by the advertisers. The signs used also can attract the attention of the audience as well as to persuade them to buy or use the products. The data of this study were taken from the internet. The process of collecting data was searching the data from the internet, downloading the data and note taking technique. The data were analyzed by descriptive qualitative method. This study used the theory of semiotics by (Saussure, 1983) to find out the verbal and non-verbal signs and the theory of meaning by (Barthes, 1967) and supported by theory of color by (Wierzbicka, 1996). By conducting of this study, it found that verbal and non-verbal signs have important rules to make an attractive advertisement. These verbal and non-verbal signs contain denotation and connotation meaning. The advertiser tends to use brief sentences and give an informative idea about the event that held in order to attract reader’s attention. The pictures, the models, and the colors used in the advertisements also support the sentences in delivering the idea. Both of verbal and non-verbal signs are related to each other since what is in verbal signs are conveyed in visual signs.